Ewing Sarcoma of the Craniofacial Bones: A Qualitative Systematic Review. (April 2022) - Rehman, Rafey; Osto, Muhammad; Parry, Nathan; Awada, Nadeen; Agemy, Jacob; Arianpour, Khashayar; Folbe, Adam J.
Objectives: To conduct a systematic review on the demographics, characteristics, management, treatment, complications, and outcomes of Ewing sarcomas in the craniofacial bones. Data Sources: Using Cochrane Library, EmBase, and PubMed, the authors identified 71 studies to be included. Review Methods: The Cochrane Library, EmBase, and PubMed databases were used to identify literature relating to Ewing sarcomas in the craniofacial bone to conduct a systematic review. Patient demographics, clinical characteristics, and treatment strategies were extracted. Results: Seventy-one studies encompassing 102 patients were identified. The most common craniofacial locations involved were the frontal bone (16.7%, n = 17), nasal cavity (16.7%, n = 17), and temporal bone (14.7%, n = 15). Stratified by location, the most common presenting symptoms were frontal bone (palpable mass, n = 8, 47.1%), nasal cavities (epistaxis, n = 9, 52.9%), and temporal bones (headache, n = 5, 33.3%). The 3 most commonly used treatment strategies were a combination of surgical intervention/radiotherapy/chemotherapy (n = 43, 43%), a combination of radiotherapy/chemotherapy (n = 18, 18%), and a combination of surgical intervention/chemotherapy (n = 15, 15%). Patients who received a combination of surgical intervention/radiotherapy/chemotherapy experienced local recurrence rate of 16.6%. However, other combinations of therapies such as surgical intervention/chemotherapy and radiotherapy/chemotherapy had a lower local recurrence rate but were limited by small sample size. Most patients (79.0%) were disease free without evidence of recurrence. Conclusion: Ewing Sarcoma of the craniofacial bones has a good prognosis when treated appropriately. Given that our study was limited by retrospective data, we advise clinicians to use the findings of this article with their own clinical judgment to determine which treatment strategy they should pursue.